Understanding emotion at work - Fineman, Stephen (SAGE Publications, 2003)
Getting to the heart of what binds and breaks organizations: emotion, Stephen Fineman explores beyond the surface of work to the rich emotional life bubbling underneath, showing what employees and managers constantly deal with but are often ill-equipped to do so.